Methodology for improving speed and strength endurance of qualified taekwondo athletes at the stage of improving their sports skills - Misbakhov, A.; Zalyalieva, O.; Sungatullin, R. (Theory and Practice of Physical Culture, 2025)
Purpose of the study. To theoretically substantiate the methodology for improving speed and strength endurance in qualified taekwondo athletes at the stage of improving their sports skills.